Sketch Based Photographs Retrieval System (International Journal of Engineering and Computer Science, 2017)
The image retrieval technique uses so many methods for retrieving related images from various database systems. Sketch based retrieval of image also used for many purposes in the cyber activity or any other search engine. The aim of this paper is to retrieve the images from the database based on the sketch that the use drawn. Here we consider the attributes of sketch and compare the sketches with the related images. The features of sketches like color (RGB format) edge points, lines, circles, rectangles, and straight lines for comparing with the related images. And after comparing these images we are trying to retrieve the refined result of users sketch .That means the user can view the accurate results with maximum clarity. The paper concerns with the effective and quality results of user search and here we apply the different vision techniques to extract the features of the sketch.